Exploring the Use of Environmental DNA (eDNA) to Detect Animal Taxa in the Mesopelagic Zone - Govindarajan, Annette F.; Francolini, Rene D.; Jech, J. Michael; Lavery, Andone C.; Llopiz, Joel K.; Wiebe, Peter H.; Zhang, Weifeng (Gordon) (Frontiers in Ecology and Evolution, 2021)
Animal biodiversity in the ocean’s vast mesopelagic zone is relatively poorly studied due to technological and logistical challenges. Environmental DNA (eDNA) analyses show great promise for efficiently characterizing biodiversity and could provide new insight into the presence of mesopelagic species, including those that are missed by traditional net sampling. Here, we explore the utility of eDNA for identifying animal taxa. We describe the results from an August 2018 cruise in Slope Water off the northeast United States. Samples for eDNA analysis were collected using Niskin bottles during 5 CTD casts. Sampling depths along each cast were selected based on the presence of biomass as indicated by the shipboard Simrad EK60 echosounder. Metabarcoding of the 18S V9 gene region was used to assess super-specific taxonomic diversity. Environmental DNA metabarcoding results were compared with those from net-collected (MOCNESS) plankton samples. We found that the MOCNESS sampling recovered more animal taxa, but the number of taxa detected per liter of water sampled was significantly higher in the eDNA samples. Environmental DNA was especially useful for detecting delicate gelatinous animals which are undersampled by nets. We also detected eDNA changes in community composition with depth, but not not with sample collection time (day vs. night). We provide recommendations for applying eDNA in the mesopelagic including the need for studies enabling interpretation of eDNA signals and improvement of barcode reference databases.